Pengaruh Meditasi terhadap Penurunan Tekanan Darah pada Penderita Hipertensi - Ni Kadek Diah Purnamayanti; Kadek Andal Martadi Prianugraha; Kadek Ariesta Mahayasa; Gusti Kadek Dedi Praja Kusuma (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2021)
Hypertension is a chronic disease that causes the highest cardiovascular complications in the world. This has implications for long-term treatment in the form of pharmacological therapy which requires substantial funding. However, pharmacological therapy alone is not effective in lowering blood pressure. The complementary therapy as a support is needed to modify the increase in blood pressure, such as meditation. Meditation is a complementary therapy based on mind body manipulation which is expected to have a relaxing effect for people with hypertension. This study aims to analyze the effect of meditation on reducing blood pressure in patients with hypertension. Methods: This integrative literature review study uses 4 online search engines, including Google Scholar, Pubmed, Sciencedirect and Garba Reference Digital (Garuda). The inclusion criteria used are articles that use original research in the 2016-2021 range. Meanwhile, the exclusion criteria apply if they are not included in the experimental design and the full text cannot be accessed. The articles obtained were assessed for quality using critical appraisal, the Olsen-Baisch Scoring. There are 10 research articles in which the use of meditation therapy has a significant effect in lowering blood pressure for people with hypertension. The use of non-pharmacological meditation therapy can be used by health workers to provide interventions to patients so that they can improve blood pressure control efforts to make decisions in choosing alternative hypertension treatments.